Q&A: Women, information access and rural development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Helen Hambly Odame argues that the provision of information to women is less important than ensuring equitable access to information.